Meenan, James - an appreciation - Anonymous (Economic & Social Studies, 1987)
Professor James Meenan, who died in Dublin on 25th May 1987 was born on 18th October 1910, the eldest son of Dr James N . Meenan who was a Professor of the faculty of Medicine at University College, Dublin. He was educated at the Catholic University School, Clongowes Wood and University College, Dublin. He won the Arkin medal for Irish History at his First Arts examination and he went on to take first place and first class honours in the BA degree in Political Economy. In 1932 he gained the MA degree, the Coyne Memorial Scholarship and the National University of Ireland Travelling Studentship in Economics which led to studies at the Universities of Rome and Perugia and resulted in a book on the Italian Corporate State. He then studied law, was called to the bar and practised for some years. During the 1940s James Meenan concentrated on economics, which he taught at University College, Dublin.
Keywords: James Meenan - Obituary; Economists - Ireland